Flavonoid Metabolism - Recent Advances and Applications in Crop Breeding 2023
DOI: 10.5772/intechopen.108637
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids Biosynthesis in Plants as a Defense Mechanism: Role and Function Concerning Pharmacodynamics and Pharmacokinetic Properties

Abstract: Flavonoids are a major class of secondary metabolites that comprises more than 6000 compounds that have been identified. They are biosynthesized via the phenylpropanoid metabolic pathway that involves groups of enzymes such as isomerases, hydroxylases, and reductases that greatly affect the determination of the flavonoid skeleton. For example, transferase enzymes responsible for the modification of sugar result in changes in the physiological activity of the flavonoids and changes in their physical properties,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 224 publications
(198 reference statements)
0
6
0
Order By: Relevance
“…Therefore, creating novel, safer anti-inflammatory nutraceuticals is clinically relevant and may greatly impact treating inflammatory responses. Marine extracts and functional foods are comparatively undiscovered sources of potential anti-inflammatory compounds . Different polyphenolic compounds were found in the extracts, such as chlorogenic acid, one of the world’s most abundant polyphenols.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, creating novel, safer anti-inflammatory nutraceuticals is clinically relevant and may greatly impact treating inflammatory responses. Marine extracts and functional foods are comparatively undiscovered sources of potential anti-inflammatory compounds . Different polyphenolic compounds were found in the extracts, such as chlorogenic acid, one of the world’s most abundant polyphenols.…”
Section: Discussionmentioning
confidence: 99%
“…Marine extracts and functional foods are comparatively undiscovered sources of potential anti-inflammatory compounds. 37 Different polyphenolic compounds were found in the extracts, such as chlorogenic acid, one of the world’s most abundant polyphenols. Accumulated evidence has shown that chlorogenic acid possesses multiple biological activities, including antibacterial, antioxidant, anti-Alzheimer’s, and anticarcinogenic.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to acting as UV filters, signal molecules, allopathic chemicals, phytoalexins, detoxifying agents, and antimicrobials, flavonoids protect plants against biotic and abiotic stress [ 68 ]. The anti-pathogenic properties of flavonoids may result from their antioxidant properties influencing the deactivation of ROS generated by both pathogens and the plant as a result of infection [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Polyphenols belonging to the flavonoid group (flavonols, flavones, flavanones, flavanols, isoflavones, and anthocyanins) all have in their structure two benzene rings linked by a heterocyclic pyrone C-ring, existing in foods, and they are found as glycosides, C-glycosides, and O-glycosides, flavan-3-ols not conjugated [ 190 ].…”
Section: Crosstalk Between Dietary Polyphenols and Gut Microbiotamentioning
confidence: 99%